Robin Hood stage 6 - Hunt, Roderick (Oxford, United Kingdom Oxford University Press, 2012)
"Robin Hood(3y (Bfrom the ORT series centers around a school outing to see a pantomime production of Robin Hood. During the performance, the children$1 (BBiff, Kipper, Aneena, and others$1 (Bfind that their magic key begins to glow, transporting them into a real-life interaction with Robin Hood and the Sheriff of Nottingham. The story offers an engaging blend of familiar historical legend with the excitement of magical adventures